American fictions, 1940-1980 a comprehensive history and critical evaluation. - Karl, Frederick R. (Frederick Robert), 1927-2004 (Harper & Row, 1983)
This comprehensive, critical analysis of American novels of the past four decades interprets and evaluates a wide range of writers and works of what Karl views as the first sustained period of "American Modernism."